Institutional development or direct support to the poor - Neil Webster (Danish Institute for International Studies (DIIS), 2009)
Success with direct support to the poor is highly dependent on the particular context in which it is implemented. Cash Transfer Programmes, handing over funds directly to poor households - typically on certain conditions, such as school attendance of the children - have the potential of creating demand for institutional change from below. In this way consensus that development cooperation should first of all seek to create an enabling institutional environment for poverty reduction has been challenged. But there are no magic bullets. Neil Webster takes a look at the various initiatives.
Keywords: 330; Entwicklungshilfe; Entwicklungstheorie